A Framework for Social Ontology. (March 2016) - Epstein, Brian
This paper sets out an organizing framework for the field of social ontology, the study of the nature of the social world. The subject matter of social ontology is clarified, in particular the difference between it and the study of causal relations and the explanation of social phenomena. Two different inquiries are defined and explained: the study of the grounding of social facts, and the study of how social categories are "anchored" or set up. The distinction between these inquiries is used to clarify prominent programs in social theory, particularly theories of practice and varieties of individualism.